Development of Indonesian language teaching materials in vocational high schools: integrating digital literacy in news writing - Saep Lukman; Iis Ristiani; Neng Wina Resky Agustina (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to develop Indonesian language teaching materials based on news writing for grade XI vocational high school (SMK) students. The approach used is descriptive-qualitative with a case study method conducted at SMK Vancanity Pacet Cianjur, integrating digital literacy, character value development, and project-based learning approaches. Data were collected through curriculum review, teaching material analysis, trial implementation at SMK Vancanity Pacet Cianjur, and evaluation based on questionnaires and interviews. The results show that the development of instructional materials that are adaptive to the Merdeka Curriculum enhances students’ factual literacy, 21st-century skills, and social responsibility. Emphasis on the integration of digital technology, such as creating vlogs and news posters, increases the attractiveness and relevance of the material. Recommendations are directed at strengthening effective lead writing practices, using professional online media, and developing interactive instructional materials.